Pandemic strains of Escherichia coli causing extraintestinal diseases: a genomic analysis of ExPEC from human and poultry sources - Saidenberg, André Becker Simões (2024)
Escherichia coli causing extra-intestinal infections (ExPEC) is a worldwide emerging pathogen causing urinary tract infections (UTIs), sepsis, meningitis, and other extra- intestinal diseases. ExPEC can also affect other species, of which poultry are severely affected by avian pathogenic E. coli (APEC) outbreaks. Some groups of avian strains share many similarities in their virulence repertoire while belonging to the same clonal lineages as isolates causing disease in humans, which suggests that poultry isolates is an underrated zoonosis. In addition to these characteristics, antimicrobial resistance (AMR), including against critically important antibiotics which are frequently carried on mobile genetic elements, expand the potential contribution to human disease. This thesis analyzed, in depth, different clonal lineages that can be detected in poultry as well as infecting humans, while performing comparisons with international isolates from varied sources to obtain a better understanding of the zoonotic potential posed by such isolates. Three separate studies were carried out, utilizing phenotypic analyses as well whole genome sequencing of isolates from the ST73, ST131-H22, and ST117 clonal lineages originating from poultry outbreaks in Brazil. The overall results, though different for each lineage regarding the importance of virulence and/or AMR carriage, suggests not only a zoonotic potential but strongly supports, as in the case of the ST117 analyses, a poultry origin for human infections. These results add to the growing evidence of the foodborne zoonotic origin contributing to a yet unquantified number of human infections.